2020
DOI: 10.3390/jpm10030130
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Data Mining Repurposes the JAK2 (Janus Kinase 2) Inhibitor Fedratinib for Treating Pancreatic Ductal Adenocarcinoma by Reversing the KRAS (Kirsten Rat Sarcoma 2 Viral Oncogene Homolog)-Driven Gene Signature

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is still one of the most aggressive and lethal cancer types due to the late diagnosis, high metastatic potential, and drug resistance. The development of novel therapeutic strategies is urgently needed. KRAS (Kirsten rat sarcoma 2 viral oncogene homolog) is the major driver mutation gene for PDAC tumorigenesis. In this study, we mined cancer genomics data and identified a common KRAS-driven gene signature in PDAC, which is related to cell–cell and cell–extracellular matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…However, in nearly one-third of patients, cancerous growth has already spread to regional lymph nodes at the time of diagnosis [67]. Therefore, it is necessary to investigate novel prognostic techniques for early-stage detection, which employ new biomarkers in a vital role [68][69][70][71][72][73]. Furthermore, characterizing the immune system, profiling the TME, and constructing BRCA immunotherapies are also known as critical keys in cancer research [74,75].…”
Section: Discussionmentioning
confidence: 99%
“…However, in nearly one-third of patients, cancerous growth has already spread to regional lymph nodes at the time of diagnosis [67]. Therefore, it is necessary to investigate novel prognostic techniques for early-stage detection, which employ new biomarkers in a vital role [68][69][70][71][72][73]. Furthermore, characterizing the immune system, profiling the TME, and constructing BRCA immunotherapies are also known as critical keys in cancer research [74,75].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, a recent study from Liu et al. found that TG-101348 could exhibit KRAS-dependent anticancer activity in pancreatic ductal adenocarcinoma cell [101] . Vinorelbine is a common chemotherapy medication for the treatment of non-small cell lung cancer and other types of cancer [ 102 , 103 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phase 2 clinical trial of TG-101348 on patients with ruxolitinibresistant or ruxolitinib-intolerant myelofibrosis showed that patients could obtain significant clinical benefit with TG-101348 [100]. Besides, a recent study from Liu et al found that TG-101348 could exhibit KRAS-dependent anticancer activity in pancreatic ductal adenocarcinoma cell [101]. Vinorelbine is a common chemotherapy medication for the treatment of non-small cell lung cancer and other types of cancer [102,103].…”
Section: Discussionmentioning
confidence: 99%
“…Due to their expeditiousness and robustness in screening potential targets in diseases, high-throughput technologies are now playing critical roles in the biomedical fields. Various publicly available databases, including Gene Expression Omnibus (GEO), which covers more than 94,000 datasets and over 2 million samples, are widely employed in cancer research for both raw and processed dataset analyses [ 21 , 22 , 23 , 24 , 25 , 26 ]. Oncomine is mainly applied to numerous cancer types and subtypes to query mRNA gene expression profiles, and it offers multiple types of analysis, allowing researchers to compare variations in gene expressions between matched tumor and normal tissues [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%